Oral health care for the elderly population in Malaysia: A review of current status and future direction - Ahmad, Mas Suryalis; Razak, Ishak Abdul; Borromeo, Gelsomina Lucia (SEAMEO Regional Tropical Medicine and Public Health Network, 2018)
Poor oral health status among the elderly population in Malaysia could be associated with various limitations in accessing oral health care services experienced by these individuals. This review discusses government policies and services available to support oral health needs of the elderly population in Malaysia. It also discusses the current status of oral health and dental treatment needs of this patient cohort, as well as the level of utilization of oral health care services. Recommendations to address the various issues are provided to serve as guidance to policy makers in formulating an effective plan aimed at improving the status of oral health and the services available for elderly individuals in the country.